2017
DOI: 10.1002/erv.2501
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up Assessment of Cognitive Remediation Therapy in Adolescent Anorexia Nervosa: A Pilot Study

Abstract: Results provide a first insight into follow-up-assessments of CRT in adolescent AN. More randomized controlled studies are needed to clarify the long-term effects of CRT. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 79 publications
(151 reference statements)
1
34
0
Order By: Relevance
“…An inpatient case series (n = 20) found significant improvements in a number of neuropsychological functions, including visuospatial (Lindvall Dahlgren, Lask, Landrø, & Rø, 2013). A subsequent follow-up trial using this same sample, with some additional participants (n = 33), compared individuals with AN who received CRT to those who received no additional treatment (Herbrich et al, 2017). Compellingly, this study found improvements in cognitive flexibility following the intervention (using different neuropsychological tests), whereas the healthy controls showed no improvement over the same time period.…”
Section: Study Characteristicsmentioning
confidence: 76%
See 3 more Smart Citations
“…An inpatient case series (n = 20) found significant improvements in a number of neuropsychological functions, including visuospatial (Lindvall Dahlgren, Lask, Landrø, & Rø, 2013). A subsequent follow-up trial using this same sample, with some additional participants (n = 33), compared individuals with AN who received CRT to those who received no additional treatment (Herbrich et al, 2017). Compellingly, this study found improvements in cognitive flexibility following the intervention (using different neuropsychological tests), whereas the healthy controls showed no improvement over the same time period.…”
Section: Study Characteristicsmentioning
confidence: 76%
“…However, this analysis may have been compromised because of two studies from the same research group using overlapping samples (Herbrich et al, 2017;van Noort et al, 2016). However, the meta-analysis of common outcome measures indicated small effect size improvements in central coherence following CRT for individuals, suggesting that YP exhibited a gestalt information processing style following CRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, fewer studies have addressed the application of CRT for young patients with AN and findings have been mixed (for review, see Tchanturia, Giombini, Leppanen, & Kinnaird, 2017). Some recent evidence suggests improved set-shifting abilities for adolescents with AN following CRT (Harrison et al, 2018), which supports further investigation using randomized controlled trials (Herbrich et al, 2017;Lock, Fitzpatrick, Agras, Weinbach, & Jo, 2018;Timko, Goulazian, Fitzpatrick, & Rodriguez, 2018).…”
Section: Introductionmentioning
confidence: 99%